PENERAPAN TEKNOLOGI KOMPUTASI AWAN (CLOUD COMPUTING) UNTUK PEMBELAJARAN MAHASISWA DI PERGURUAN TINGGI - Intan Mutia (Faktor Exacta, 2016)
Development of Internet-based computing technology today is more directed to the system easy application without requiring a lot of time and effort. In the presence of cloud computing in the digital era has now actually been felt in the community in their daily lives such as the use of email and social media. The general objective of this study is to explore the application of cloud computing technology (cloud computing) for students to be able to store computerized learning material according to the material provided by the teachers so that they can assist learning system effectively and efficiently. The results of this study can help students in understanding and application of cloud computing technology functions primarily in learning. This research is a case study with a qualitative descriptive approach using interviews and questionnaires instrument. The results of the analysis mentioned above shows that most users use the cloud (cloud computing) by all the conveniences offered by this app when compared to conventional learning system which is performed in the classroom. The facilities presented by cloud computing applications become an attraction for students.Keywords: application, cloud computing, komputasi awan, learning